Global Administrative Law and EU Administrative Law Relationships, Legal Issues and Comparison - Chiti, Edoardo; Mattarella, Bernardo Giorgio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book seeks to enrich and refine global administrative law and EU administrative law analytical tools by examining their manifold relations. Its aim is to begin to explore the complex reality of the interactions between EU administrative law and global administrative law, to provide a preliminary map of such legal and institutional reality, and to review it. The book is the first attempt to analyze a dense area of new legal issues. The first part of the book contains core elements of a general theory of the relationships between global and EU administrative law: comparative inquiries, exchanges of legal principles, and developing linkages. The second part is devoted to special regulatory regimes, in which global and European law coexist, though not always peacefully. Several sectors are considered: cultural heritage, medicines, climate change, antitrust, accounting and auditing, banking supervision, and public procurement.
Introduction -- A. Cross-Section Analysis: Comparative Inquiries -- Exchanges of Legal Principles -- Developing Linkages and Networks -- B. Sectoral Analysis: Parallel Regimes -- Converging Harmonizations -- Cross Implementations.
Keywords: Law; Comparative law; Public law; Administrative law; Law; European Law/Public International Law; Administrative Law; International & Foreign Law/Comparative Law